1986
DOI: 10.1002/ijc.2910380608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mass screening program for stomach cancer with a case‐control study design

Abstract: In order to evaluate the effectiveness of a mass screening program for stomach cancer, a case-control study was conducted in Nose town in Osaka, Japan. The case series consisted of all deaths from stomach cancer during the period 1969-1981 (54 in males and 37 in females). For each case, 3 controls of the same sex and from the same precinct as the case, and born within 5 years of the case birth-year, were selected at random from Nose town residents alive at the date of death of the relevant case. We then invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 6 publications
2
98
1
5
Order By: Relevance
“…Only one randomized trial has been reported, 33 and, although no results were available at the time, it is highly unlikely that, given the small difference in screening experience between intervention and control groups, any benefit could emerge later. Three case control studies, of prevention of cancer deaths 6,35 or of advanced disease, 36 all suggested a beneficial effect of screening, as did 2 prospective cohort studies comparing mortality rates in individuals participating or not in the mass screening program. 37,38 The study in Osaka 37 showed a rather higher than expected incidence of gastric cancer in individuals undergoing screening, implying possible overdiagnosis (detection of nonprogressive "cancer") in this group.…”
Section: Respective Roles Of Lifestyle and Screeningmentioning
confidence: 99%
“…Only one randomized trial has been reported, 33 and, although no results were available at the time, it is highly unlikely that, given the small difference in screening experience between intervention and control groups, any benefit could emerge later. Three case control studies, of prevention of cancer deaths 6,35 or of advanced disease, 36 all suggested a beneficial effect of screening, as did 2 prospective cohort studies comparing mortality rates in individuals participating or not in the mass screening program. 37,38 The study in Osaka 37 showed a rather higher than expected incidence of gastric cancer in individuals undergoing screening, implying possible overdiagnosis (detection of nonprogressive "cancer") in this group.…”
Section: Respective Roles Of Lifestyle and Screeningmentioning
confidence: 99%
“…As summarized in Table 3, three cohort studies have examined the effect of the screening [34][35][36]. Oshima et al [34] followed up 32 789 residents in a town of Osaka Prefecture who were screened at least once during 1967-1970.…”
Section: Cohort Studymentioning
confidence: 99%
“…Efficacy has been evaluated only for barium meal examinations in Japan by case -control studies (Oshima et al, 1986;Fukao et al, 1995;Mizoue et al, 2003). 18 F-2-deoxy-2-fluoro-glucose Positron Emission Tomography is more expensive than the other two procedures (85 000 Japanese yen or 772 US$ for FDG-PET, 12 680 yen or 115 US$ for endoscopy in our screening program, and about 82 US$ for barium meal examination).…”
Section: Discussionmentioning
confidence: 99%
“…For early detection of gastric cancer, X-ray examination with a barium meal has been employed in Japan (Fukao et al, 1995). Efficacy of this kind of screening program has been strongly suggested, although the studies are observational (Oshima et al, 1986;Fukao et al, 1995;Mizoue et al, 2003). The problem with the program is that the screening test is somewhat invasive in terms of complications such as constipation being frequently seen and mis-swallowing of barium into the trachea (Tamura et al, 1985;Sugahara et al, 1992).…”
mentioning
confidence: 99%